Formulating the Strategy for Agrotourism Destinations: Nglingoo Tourism Vilage, Samigaluh, Kulon Progo - Murtini, Umi; Hardiyanto, Purnawan (European Scientific Journal, ESJ, 2023)
This study aims to develop the strategy to attract tourists to visit the Nglinggo tea plantation as a tourist destination in Samigaluh, Kulon Progo Regency. The research data used primary data which was collected using interviews, filling out questionnaires and focus group discussions. The data were obtained from the tourists who are visiting the Nglinggo tea plantation, the tour managers and Pager Harjo village officials. The analysis tools used the External Factor Evaluation Matrix (EFE), Internal Factor Evaluation Matrix (IFE) and the Quantitative Strategic Planning Matrix (QSPM). From the results of the IFE and EFE matrices, then SWOT table is compiled to obtain several alternative strategies. The alternative strategies that exist are analyzed using QSPM to get the right strategy. The results of the analysis obtained IFE and EFE values above the average. The educational value of picking and processing tea and its culture had a greater value than its weaknesses, namely the destruction by tourists, lack of roads and electricity infrastructures. The external environmental conditions that become the opportunities are the changes in people’s lifestyles, the support from the government for tourism development and the good image by tourists. The strategic options that can be taken are: making the activity of drinking tea as a tradition in Indonesia, increasing the educational tours of picking and processing tea, working with the government to build roads that facilitate the tourist to get to the tourist attractions safer and increasing the electrical installations around the tourist attractions as well as educating the public and the tourists about the conservation of the environment.